Persepsi Masyarakat Terhadap Taman Bacaan Masyarakat (TBM) Sebagai Sarana Pengetahuan dan Keterampilan di SKB 1 Tanah Datar - Fira Rahma Putri Arya; Marlini Marlini (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2024)
This research aims to analyze the public's perception of the Community Reading Garden (TBM) as a means of knowledge and skills in SKB 1 Tanah Datar. The type of research used is quantitative with descriptive research methods. The population used was 983 with a sample of 91 people. Based on the results of the analysis, it shows positive perceptions in three aspects: cognitive, affective and conative. The cognitive aspect obtained an average score of 2.79 indicating a good understanding of TBM, but the collection of books for skills activities needs to be improved. The affective aspect obtained an average score of 3.05 indicating high enthusiasm for TBM activities, especially the skills program. The conative aspect obtained an average score of 2.93 indicating high interest in participating in TBM activities, even though the frequency of borrowing books is relatively low. In conclusion, TBM at SKB 1 Tanah Datar has great potential as a community learning center, but still requires development in terms of book collections, skills programs, and strategies to increase interest in borrowing books.